2016
DOI: 10.1093/inthealth/ihw016
|View full text |Cite
|
Sign up to set email alerts
|

Interpretations of education about gene-environment influences on health in rural Ethiopia: the context of a neglected tropical disease

Abstract: BackgroundMisunderstandings of the role of genetics in disease development are associated with stigmatizing behaviors and fatalistic attitudes about prevention. This report describes an evaluation of community understanding of an educational module about genetic and environmental influences on the development of podoconiosis, a neglected tropical disease endemic in highland Ethiopia.MethodsA qualitative process assessment was conducted as part of a large prospective intervention trial in August 2013, in Wolait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Barefoot exposure to soil was also raised by children as a cause of podoconiosis though the role of mineral particles in the soil was mentioned infrequently. This is congruent with previous studies which reported poor knowledge of adult community members about mineral particles in the soil as a causal agent of podoconiosis [ 8 10 , 12 , 43 , 44 ]. Regarding preventive measures, children were well aware of the importance of footwear and foot hygiene.…”
Section: Discussionsupporting
confidence: 92%
“…Barefoot exposure to soil was also raised by children as a cause of podoconiosis though the role of mineral particles in the soil was mentioned infrequently. This is congruent with previous studies which reported poor knowledge of adult community members about mineral particles in the soil as a causal agent of podoconiosis [ 8 10 , 12 , 43 , 44 ]. Regarding preventive measures, children were well aware of the importance of footwear and foot hygiene.…”
Section: Discussionsupporting
confidence: 92%
“…The Tome Gerira and Sura Koyo kebeles were selected because neither had been targeted in previous studies of podoconiosis. 19 , 20 , 26 …”
Section: Methodsmentioning
confidence: 99%
“…Previous work on the African continent has illustrated that genomic information could be a tool to reduce gendered blame by fostering dialogue about the role of biology and inheritance in disease causation ( Marsh et al, 2011 ). Community-based interventions may be successful in countering such narratives ( Tora et al, 2016 ). Yet what our experience demonstrated is that it is not straightforward to use genomic explanations of illness to foster discussions about gendered blame in an environment where there is apparent factual evidence to support it.…”
Section: Examples Where the Design And Conduct Of mentioning
confidence: 99%